2015
DOI: 10.1111/trf.13369
|View full text |Cite
|
Sign up to set email alerts
|

Response of steroid‐refractory chronic graft‐versus‐host disease to extracorporeal photopheresis correlates with the dose of CD3+ lymphocytes harvested during early treatment cycles

Abstract: Our data suggest that CD3+ cell evaluation in ECP during the early phase of treatment course could predict response and help identify patients who deserve further treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…ECP is an immunoregulatory therapy widely used in different pathologies including acute and chronic GvHD. Although its mechanism of action is still unclear, previous studies have described a correlation between the amount of MNC infused and the overall response to treatment . This study reports a retrospective comparison of the performance of the COBE Spectra Auto‐PBSC program and the Spectra Optia (MNC and CMNC) protocols to collect MNC for “off‐line ” ECP in GVHD patients.…”
Section: Discussionmentioning
confidence: 99%
“…ECP is an immunoregulatory therapy widely used in different pathologies including acute and chronic GvHD. Although its mechanism of action is still unclear, previous studies have described a correlation between the amount of MNC infused and the overall response to treatment . This study reports a retrospective comparison of the performance of the COBE Spectra Auto‐PBSC program and the Spectra Optia (MNC and CMNC) protocols to collect MNC for “off‐line ” ECP in GVHD patients.…”
Section: Discussionmentioning
confidence: 99%
“…A study among six centers reviewed outcomes for 94 patients undergoing ECP and found a 91% complete remission (CR) for acute GVHD and a 45% CR and a 35% partial remission for steroid‐refractory chronic GVHD, with a median follow‐up of 27 months and a 90% survival for the chronic GVHD patients at that time . Another study showed 67% partial remission and 53% CR in 15 patients with chronic GVHD who underwent a total of 726 procedures, and the response was correlated with the number of CD3+ lymphocytes . When analyzing skin GVHD outcomes, improvement was demonstrated in nine of 29 patients (31%), including in a randomized controlled trial at multiple sites with an 86% completion rate after 24 weeks, in patients who did not improve or worsened while receiving immunosuppressive therapy without ECP …”
Section: Resultsmentioning
confidence: 99%
“…Generally, acute GVHD (Grade II‐IV) is treated with two to three treatments per week with a taper to two weekly, then two every 2 weeks until a response occurs . For chronic GVHD, the following or similar regimens have been used or recommended: 2 days back‐to‐back (one cycle) every 1 to 2 weeks performed weekly or every other week until a response is observed or treatment is performed for 8 to 12 weeks, tapered to every 2 to 4 weeks until a response occurs …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two studies have suggested a possible link between the total number of mononuclear cells (MNCs) treated in children with cGVHD and the outcome. 10 However, the clinical efficacy of a small-scale ECP calls into question this dose effect in the setting of aGVHD: by reinfusion of about ten times fewer cells than with conventional ECP, the authors reported an intriguing efficacy. 5,11 Although the exact mechanism of action of ECP remains largely unclear, the hypothesis of T-cell vaccination 12 supports this relative absence of cell-dose effect.…”
mentioning
confidence: 99%